THE EFFECT OF ORGANIZATIONAL COMMITMENT AND WORK ENVIRONMENT ON THE WORK DISCIPLINE OF VILLAGE OFFICIALS IN PULO VILLAGE CIRUAS DISTRICT - WIJAYA, PRIATNA (DESANTA (Indonesian of Interdisciplinary Journal), 2024)
The purpose of this study is to determine the influence of organizational commitment on employee work discipline, to find out the influence of the work environment on employee work discipline and to find out the influence of organizational commitment and organizational commitment together on employee work discipline in Pulo Village, Ciruas District. The population in this study is 42 people, while the sample with the saturated sample method was obtained from a sample of 42 respondents in Pulo Village, Ciruas District. The results of this study in the first hypothesis there is a significant influence of organizational commitment on employee work discipline in pulo Village, CiruasDistrict, the results of tcount > ttable (6.188 > 2.021) with a significance level of 0.00 (0.00 < 0.05), the second hypothesis there is a significant influence of the work environment on employee work discipline in Pulo Village, Ciruas District, tcount > ttable (3.115 > 2.021) with a significance level of 0.00 (0.00 < 0.05) and The third hypothesis is that there is a significant influence of organizational commitment and work environment simultaneously on the work discipline of employees in Pulo Village, Ciruas District.obtained the results of Fcal > Ftabel (24,612 > 3,238) with a significance level of 0.00 (0.00 < 0.05). The conclusion of this study is that the first hypothesis has a significant influence of organizational commitment on employee work discipline in Pulo Village, Ciruas District. The second hypothesis is that there is a significant influence of the work environment on employee work discipline in Pulo Village, Ciruas District and the third hypothesis is that there is a significant influence of organizational commitment and work environment simultaneously on employee work discipline in Pulo Village, Ciruas District.